Професійна післядипломна освіта вчителів початкової школи: виклики та досвід республіки Австрія - Осередчук Ольга; Olga Oseredchuk; Марусинець Маріанна; Maruszinec Marianna; Marianna Marusynets (Видавництво «Код», 2024)
Резюме. У статті порушено питання професійної післядипломної освіти учителів початкової школи в українському контенті та з опорою на закордонний досвід – Республіку Австрія, окреслено пріоритетні напрями, які можуть бути корисними для впровадження та імплементації законодавчо – нормативних актів та практико-орієнтованих напрямів сучасного реформування післядипломної педагогічної освіти. До базових австрійські вчені залічують: рівне право громадян здобувати освіту рідною мовою; надання вчителям, у тому числі початкових класів, статусу державних службовців, врахування потреб суспільства, освітніх завдань, гуманістичний і демократичний характер, наступність освітніх ланок, аполітичність, життєві та соціальні чинники, обов’язковість, світськість, аполітичність.

Abstract. The article deals with the issue of professional postgraduate education of primary school teachers in the Ukrainian content and based on foreign experience–- the Republic of Austria, outlines priority areas that may be useful for the introduction and implementation of legislative, regulatory and practice-oriented foundations of modern reform of postgraduate teacher education. Austrian scholars include the following basic principles: equal right of citizens to receive education in their native language; granting teachers, including primary school teachers, the status of civil servants, the needs of society, its tasks, life and consideration of circumstances; humanistic and democratic nature, compulsory, secular, apolitical, taking into account the continuity of all its links. It is concluded that the Austrian system, which has three key guidelines: knowledge of oneself, another person and society, contributes to the teacher's ability to apply new knowledge, skills and abilities to analyse and transfer them to students using new technologies in the educational process. Its uniqueness is also characterised by openness to positive innovations, while at the same time preserving its identity, national and regional peculiarities.
Professional postgraduate education of primary school teachers: challenges and experience of the republic of Austria
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00015039 Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-10
Keywords: післядипломна освіта; вчитель початкової школи; вектори реформування; досвід Республіки Австрія